Análise das variações morfodinâmicas por funções ortogonais empíricas - Praia do Flamengo (RJ) - Cardinale-Araujo, Aline (2016)
Flamengo Beach has been modified because of the land reclamation which resulted in the advancement of the original coastline, and may be exposed to beach erosion. This research is motivated to know the morphodynamics of this beach in order to provide information for making decision in the coastal management, and to guide future works of coastal engineering. The profiles measured by survey were analyzed by EOF method (Empirical Orthogonal Functions). Also, there were performed grain size analysis, coastal circulation cells study, and satellite images analysis to provide complementary data. As a result, it was possible to determine the partitioning of the beach in 3 sectors: Sector I, where prevail beach cusps (P1, P2 and P3) through a point that is probably the transition (P4); Sector II (P5 and P6) where the beach behavior tends to reflective state; and Section III (P7 and P8), with the presence of a low-water terrace. Updrift the pier, the beach back to present cusp of beach behavior.